COVID‐19 and the spotlight on stakeholderism - KOH, Pearlie (Institutional Knowledge at Singapore Management University, 2020)
The global disrupter that is COVID-19 has profoundly impacted human life on earth. Lives and livelihoods have been lost. But even for those amongst us fortunate enough to escape such calamity, significant adjustments have had to be made to the ways in which we live, play and work. As the United Nations noted, “[t]his is much more than a health crisis. It is a human, economic and social crisis. The coronavirus disease … is attacking societies at their core”.